Exigência de lisina e estimativa dos aminoácidos essenciais para tambaqui, colossoma macropomum (cuvier, 1818) - Costa, Edimar Lopes da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Lysine is one of the most limiting amino acids in aquafeeds due to its importance in fish body protein deposition. Therefore, lysine requirement studies are needed to optimize diets for aquaculture, especially for species such as tambaqui. In order to determine lysine requirement by dose-response method and estimate the requirement of essential amino acidsbased on ideal protein concept, tambaquis juveniles (7.7 ± 0.06 g) were distributed in 500-L tanks, in a completely randomized design. Fish were fed semipurified diets formulated with casein, gelatin and free amino acids premix, containing increasing six levels of lysine (L-lysine HCL 0.9, 1.2, 1.5, 1.8, 2.1 and 2.4%). Increasing levels of lysine did not affect tambaqui performance parameters, then it was not possible to estimate the lysine requirement by doseresponse curve. Tambaqui presented feed intake reduction, low weight gain and high feed conversion probably by the low palatability of semipurified diets. These diets significantly affected hematologic parameters hematocrit (Ht), hemoglobin concentration [Hb] and red blood cel count (RBC), but with no tendency by increasing lysine levels. Physiological parameters as cholesterol, triglycerides and plasma cortisol showed significant differences (p <0.05) between treatments. Fish fed the lowest level of dietary lysine showed the highest values for cholesterol and triglycerides. Plasma cortisol tended to decrease with increasing dietary lysine level. It was not possible to determine lysine requirement by dose-response method with levels from 0.9 to 2.4% dietary lysine. Essential amino acids requirement estimated by the amino acid content of whole body tambaqui based on ideal protein concept, were similar to other species and lysine requeriment was estimated at 6.0 and 6.2% of dietary protein by both methods.
Keywords: Aminoácidos no Tambaqui; Fisiologia do Tambaqui; Tambaqui